Security, Trade, and Political Violence. Issue 1 (10th January 2020) - Amodio, Francesco; Baccini, Leonardo; Di Maio, Michele
Abstract: This paper studies the effect of security-motivated trade restrictions on economic activity and political violence. We exploit the 2008 restrictions imposed by Israel on imports of selected goods to the West Bank as a quasi-experiment. We show that after 2008 (i) output and wages decrease differentially in manufacturing sectors that use restricted materials more intensively as production inputs, (ii) wages decrease in localities where employment is more concentrated in these sectors, and (iii) episodes of political violence are more likely to occur in these localities. This differential effect accounts for 16% of violent events that occurred in the West Bank from 2008 to 2012.